“The ones who are on their best behavior keep coming” - Lisa Meierotto; Rebecca Som Castellano; Carly Hyland (Journal of Agriculture, Food Systems, and Community Development)
H-2A farmworkers in the United States live in a state of liminality, navigating systemic precarity as they move between their home countries and employment in the U.S. While the H-2A program offers benefits such as legal passage across the border, a guaranteed minimum wage, housing, and transportation, the program also presents significant challenges. Some scholars claim the H-2A program is akin to modern-day slavery and argue temporary agricultural wodrkers experience unfreedom in their labor. In this paper, we share data related to H-2A farmworkers collected during a 2022 study on pesticide risk and exposure in Idaho. Drawing upon interview and survey data, we explore the precarity inherent in the H-2A program, and consider logistical, financial, and socio-emotional challenges facing H-2A workers, highlighting the experiences of a small group of farmworkers in Idaho. Through the analysis of this data, we find evidence that H-2A farmworkers in Idaho experience liminality, precarity, and unfreedom. This paper is a timely call for additional research on H-2A farmworker experiences. We highlight specific issues, concerns, and trends that warrant additional study.